Diagrammatic representation and inference : 10th International Conference, Diagrams 2018, Edinburgh, UK, June 18-22, 2018, Proceedings /: 10th International Conference, Diagrams 2018, Edinburgh, UK, June 18-22, 2018, Proceedings. (2018) - Unknown
No abstract available